2007
DOI: 10.1007/s00425-007-0530-2
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacterial volatile emissions regulate auxin homeostasis and cell expansion in Arabidopsis

Abstract: Certain plant growth-promoting rhizobacteria (PGPR), in the absence of physical contact with a plant stimulate growth via volatile organic compound (VOC) emissions, through largely unknown mechanisms. To probe how PGPR VOCs trigger growth in plants, RNA transcript levels of Arabidopsis seedlings exposed to Bacillus subtilus (strain GB03) were examined using oligonucleotide microarrays. In screening over 26,000 protein-coded transcripts, a group of approximately 600 differentially expressed genes related to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
348
1
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(378 citation statements)
references
References 62 publications
22
348
1
7
Order By: Relevance
“…A bouquet of over 25 bacterial volatile odors has been identified that trigger differential expression of approximately 600 transcripts related to cell wall modifications, primary and secondary metabolism, stress responses, hormone regulation and other expressed proteins. 9,12,13 These biologically active bacterial volatiles trigger plant growth promotion by a tissue specific re-distribution of endogenous auxin. 13 GB03 volatiles also augment Arabidopsis photosynthetic capacity by increasing photosynthetic efficiency and chlorophyll content.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A bouquet of over 25 bacterial volatile odors has been identified that trigger differential expression of approximately 600 transcripts related to cell wall modifications, primary and secondary metabolism, stress responses, hormone regulation and other expressed proteins. 9,12,13 These biologically active bacterial volatiles trigger plant growth promotion by a tissue specific re-distribution of endogenous auxin. 13 GB03 volatiles also augment Arabidopsis photosynthetic capacity by increasing photosynthetic efficiency and chlorophyll content.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,13 These biologically active bacterial volatiles trigger plant growth promotion by a tissue specific re-distribution of endogenous auxin. 13 GB03 volatiles also augment Arabidopsis photosynthetic capacity by increasing photosynthetic efficiency and chlorophyll content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of auxin in plant stress tolerance has been well established (Fu and Wang 2011; Pieterse et al 2012; Naseem et al 2015; Forni et al 2017). Based on previous studies showing the critical role of auxin signalling in controlling plant responses to VCs produced by various microbes (Zhang et al 2007; Splivallo et al 2009; Bailly et al 2014; Bitas et al 2015; Garnica-Vergara et al 2016), we investigated how VCs produced by two V. dahliae strains affect the growth of A. thaliana mutants defective in auxin influx ( aux1-7 ) or response ( tir1-1 and axr1-3 ) in the presence of 100 mM NaCl. These mutants were chosen because their growth responses to VCs produced by F. oxysporum and V. dahliae were defective (Bitas et al 2015; Li et al under revision).…”
Section: Resultsmentioning
confidence: 99%
“…The realization of this technique depends on the ability of plants to survive under heavy metal stress with high biomass production. The phytoremediation efficiency can be enhanced by increasing the heavy metal solubility and mobilization in the soil [4] and enhanced plant biomass by the help of plant growth promoting bacteria. This can be accomplished by emerging the relationship of hyper accumulator plants with plant growth promoting rhizobacteria (PGPR) like Bacillus and Pseudomonas having the ability for plant growth in adverse conditions.…”
Section: Introductionmentioning
confidence: 99%